Deskripsi Karir Menggunakan Teori John Holland pada Siswa MTs Nurul Yaqin - Rendianto, Septian; Angraeni, Tika; Putri, Tika; Sari, Sari; Maulidya, Maulidya; Heriyanto, Agus; Wiguna, Alivermana (Universitas Muhammadiyah Yogyakarta, 2022)
This research is motivated by the phenomenon of the lack of understanding of students towards self-understanding and their careers. For example, choosing a major or further study because of joining peers or the choice of parents only, then the student cannot be responsible for their future, or study in the majors that is not match their abilities, ultimately causing decreased performance, even causing the student to be expelled in college because of below-average grades. This research aims to present data related to career mapping using career inventory media for class VIII B Girls, VIII A Boys, and IX B Girls. This research used descriptive qualitative method, with the main data of career inventory tabulation and supporting data obtained through library research. Sampling technique in this research is stratified sampling with subjects in class VIII B female, VIII A male, and IX B female. The results of this research indicate the dynamics of personality classification and work interest with a career inventory in the form of students with realistic work personalities 1 student, intellectual 15 students, social 8 students, conventional 14 students, business 2 students, and artistic 8 students. While the work interests are outdoor 2 students, mechanical 5 students, computational 6 students, science 6 students, persuasive 3 students, artistic 9 students, literary 3 students, musical 7 students, social 6 students, and clerical 1 student. Through this research, data on factors that influence the choice of majors or further studies as part of each student's future career plans are presented.